The Reality of African-American Racism During The 2oth Century Depicted in Roll of Thunder Hear My Cry Novel - Fikzia, Iffah (Fakultas Ilmu Budaya, Universitas Mulawarman, 2025)
During the 20th century, several important events influenced the behaviour and way of thinking of Americans. There are also various technological innovation achievements that have significantly resurrected the American economy. The dynamics that occurred in 20th-century America also involved the issue of African-American racism. The injustice faced by the African nation is still one of the most important issues in understanding the definition of multiculturalism which they are proud of in describing the idea of American exceptionalism. Through Roll of Thunder Hear My Cry novel, this paper is interested in analyzing the reality of the lives of African Americans towards the issue of racism in the 20th century. In analyzing this paper, the researcher employs the qualitative method and utilizes Critical Race Theory (CRT) by Delgado & Stefancic. Through this research results, the issues of inequality and racism experienced by African Americans can be found in several forms during the 20th century, such as applying the separate but equal rule. Keywords: African-American, Jim Crow, Racism, Segregation, The Dynamic of the 20th